2000
DOI: 10.1161/01.str.31.8.1982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Delayed Intraischemic and Postischemic Hypothermia on a Focal Model of Transient Cerebral Ischemia in Rats

Abstract: Background and Purpose-Intraischemic mild hypothermia has been shown to be neuroprotective in reducing cerebral infarction in transient focal ischemia. As a more clinical relevant issue, we investigated the effect of delayed intraischemic and postischemic hypothermia on cerebral infarction in a rat model of reversible focal ischemia. We also examined the effect of hypothermia on the inflammatory response after ischemia-reperfusion to assess the neuroprotective mechanism of brain hypothermia. Methods-Rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 49 publications
0
53
0
4
Order By: Relevance
“…Intraischemic hypothermia delays or attenuates both ATP depletion (Ibayashi et al, 2000;Sutton et al, 1991;Welsh et al, 1990) and anoxic depolarization (Bart et al, 1998;Nakashima and Todd, 1996;Takeda et al, 2003), it also blocks glutamate release (Busto et al, 1989b;Patel et al, 1994;Winfree et al, 1996), suppresses inflammation (Kawai et al, 2000;Wang et al, 2002), maintains the integrity of the BBB (Dietrich et al, 1990;Huang et al, 1999;Kawanishi, 2003), reduces free radical production , inhibits protein kinase C translocation (Cardell et al, 1991;Shimohata et al, 2007a, b;Tohyama et al, 1998), inhibits matrix metalloproteinase expression (Hamann et al, 2004), and blocks both necrosis and apoptosis. Intraischemic hypothermia also preserves the base-excision repair pathway, which repairs oxidative damage (Luo et al, 2007).…”
Section: The Ostensible Pan-inhibitive Effects Of Hypothermiamentioning
confidence: 99%
See 2 more Smart Citations
“…Intraischemic hypothermia delays or attenuates both ATP depletion (Ibayashi et al, 2000;Sutton et al, 1991;Welsh et al, 1990) and anoxic depolarization (Bart et al, 1998;Nakashima and Todd, 1996;Takeda et al, 2003), it also blocks glutamate release (Busto et al, 1989b;Patel et al, 1994;Winfree et al, 1996), suppresses inflammation (Kawai et al, 2000;Wang et al, 2002), maintains the integrity of the BBB (Dietrich et al, 1990;Huang et al, 1999;Kawanishi, 2003), reduces free radical production , inhibits protein kinase C translocation (Cardell et al, 1991;Shimohata et al, 2007a, b;Tohyama et al, 1998), inhibits matrix metalloproteinase expression (Hamann et al, 2004), and blocks both necrosis and apoptosis. Intraischemic hypothermia also preserves the base-excision repair pathway, which repairs oxidative damage (Luo et al, 2007).…”
Section: The Ostensible Pan-inhibitive Effects Of Hypothermiamentioning
confidence: 99%
“…However, most reports suggest that mild to moderate hypothermia has no effect on the CBF level during ischemia in the penumbra (Kawai et al, 2000;Morikawa et al, 1992;Yanamoto et al, 2001). Nevertheless, one study reported that moderate hypothermia (301C) significantly reduced CBF using a diffusion-weighted imaging technique (Jiang et al, 1994).…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the experimental approach used in most studies reporting benefits of modest (301C to 341C) postischemic cooling (Ding et al, 2004;Kollmar et al, 2002;Maier et al, 2001;Zhang et al, 1993aZhang et al, , 1993b. In one such study, 331C hypothermia was initiated before reperfusion and sustained at 351C by housing at 51C, but the control group reached hyperthermic brain temperatures in excess of 391C during the 24-h interval evaluated (Kawai et al, 2000). However, in no other report was temperature monitored during an extended recirculation interval after recovery from anesthesia.…”
Section: Model-dependent Efficacy Of Hypothermic Protectionmentioning
confidence: 99%
“…PMNL accumulation is maximal at 48-72h. Attenuation of the inflammatory response may be one of the mechanisms by which hypothermia reduces ischemic neuronal injury 13,19,20 . Since it has been demonstrated that carr a g eenin is a highly reactive substance with inflammat o ry pro p e rt i e s 2 1 and brain inflammation can be induced with its subarachnoidal injection in brains of mice 2 2 , in this study we aimed to demonstrate that mild hypothermia can have neuroprotective e ffects in brains of rats submitted to inflammatory injury by means of the use of carrageenin.…”
mentioning
confidence: 99%